Terror en Costa Rica. El Diario Extra y el uso del discurso del miedo, entre 1979 y 1985 - Marchena Sanabria, Jorge (CIICLA, Universidad de Costa Rica, 2021)
This article analyzes the political and fear speeches, dominant in the Costa Rican newspaper Diario Extra, between 1979 and 1985, which correspond to tabloid narratives, which blamed former president Carazo Odio for the crisis that the country experienced. The main objective is to reconstruct the strategies that the newspaper used to create an alternative reality, in which, parallel to the supposed political corruption, miracles occurred, UFO appearances, among others. The result of this strategy was the enthronement of a sensational discourse to distract civil society, while the importance of the growing popular unrest and mass protests of those years was disregarded. This work was elaborated from theoretical referents around the sensationalism and its connections with the social control. The main sources corresponded to notes from the aforementioned newspaper and text analysis was used, looking for the main narratives, the context and the tangled discursivities that the Extra published.